Social Media Activism - Mugharbil, Raghda (2023)
This study examines Lebanese youth online activism and offline mobilization, highlighting the impact political sectarian divisions and Western imperialist narratives have on university students’ online engagement. The study builds on the theoretical frameworks of media imperialism, and the impact media imperialism has on youth knowledge, understanding, and use of social media platforms (SMPs) for online civic and political engagement. Additionally, the study examines how critical media literacy informs a media education agenda for youth in Lebanon. With this framework, this thesis investigates how some university students (N=47) deployed SMPs both to stay informed about political news, and to voice their political narratives online. The study applied qualitative focus group discussions covering youth from seven private universities and one public university in Beirut, Lebanon. This approach enabled the researcher to gather firsthand accounts about students’ online and offline engagement. A grounded theoretical approach was deployed to analyze the transcribed data, whereby quotes were coded, then compared to form categories, subthemes, and themes. The results of the focus groups highlighted six themes: The efficacy of SMPs in empowering students’ online activism by providing a diversity of local and international news. Additionally, students’ use of SMPs allowed them to voice and livestream from the ground during the protests of 2019, and enabled students to build online solidarities. The utility of SMPs in facilitating students’ ground mobilization and enabling students to unite despite sectarian and regional differences. The fear and dreads of students’ being virtually alienated both online and offline for voicing political opinion on SMPs. The deployment of critical media literacy skills by some students in evaluating Western coverage of the Middle East, in comparison to some students’ adoption of Western political news narratives about the Middle East. Finally, students’ recommendations for a critical media literacy framework that serves to empower youth online and offline activism and one that teaches about Palestine and Lebanon. The significance of the study lies in its contribution to the limited knowledge and research available on how youth in Lebanon utilize SMPs for online and offline activism. The findings shed light on the need for robust media literacy education, and stronger media laws that protect youth from online and offline abuses. Additionally, with a vigorous critical media framework, students will be empowered to use SMPs effectively to challenge mainstream and Western narratives and foster change in Lebanon.